The mortality and economic benefits of achieving air pollution standards in India - Paramita Sinha; Emily Decker; Rishi Dey; Colin John Mathews; Jennifer Lloyd; James Cajka; Prakash Doraiswamy; Maureen Cropper (Proceedings of the National Academy of Sciences, 2026)
The presence of high levels of PM 2.5 pollution is a major health threat in India. We evaluate the benefits of reducing ambient PM 2.5 and household air pollution from a 2019 baseline, when over 70% of the population of India was exposed to annual average PM 2.5 of more than 40 μg/m 3 and 56% of households burned solid fuels for cooking. We estimate the health benefits from reduced mortality that arise when lowering ambient PM 2.5 to the India standard (40 μg/m 3 ) and to two World Health Organization (WHO) interim standards (25 μg/m 3 and 15 μg/m 3 ). The benefits of the ambient standards are moderated by the high levels of household air pollution to which people are exposed due to the concavity of the exposure–response function. We therefore examine the benefits of achieving each standard paired with a 50% reduction in the percentage of households burning solid fuels. Annual mortality reductions from the combined policies exceed 300,000 lives saved for the India standard, 500,000 lives saved for the WHO 25 μg/m 3 interim standard, and 675,000 lives saved for the WHO 15 μg/m 3 interim standard. The economic benefits of each of these joint policies equal 2.2%, 3.6%, and 4.9% of Indian gross domestic product (GDP), using a Value per Statistical Life of 100 times per capita GDP. Results underscore the importance of considering household air pollution when evaluating ambient standards and the synergistic benefits of combined policies when the exposure–response function is concave.